Acute and persisting fatigue effects in bow arm musculature in competitive recurved archery athletes - Kolayis Eroglu, I.; Knicker, A.; Soylu, R.; Ertan, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In an archery competition the archer is sustained to shoot in difficult conditions as stress, wind, etc. The pulling weight is approximately 20 kg. of a bow, and the archer 144 times pull his bow in a competition. If stress or weather conditions block shooting, the archer can hold down the bow but must pull again in order to shoot his arrow in a given period. When considering of the pulling weight of the bow, to shoot arrow will be difficult for the archer. Because of these conditions, the aim of this study was to analyse the effects of fatigue on bow arm muscular activity in archery. Methods: 6 Female (Age: 16,66+3,44; Training age: 5,88+2,92) and 10 male (Age: 22,33+12,95; Training age: 4,11+2,80) subject were involved in the study. Each subject participated in double test session and each archer shooted 12 arrows before and after fatigue protocol and bow arm Deltoid Posterior, Deltoid middle, Deltoid Front part, Trapezius Middle, Trapezius Upper, Triceps Brachii, Biceps Brachii, Forearm extensors and Forearm flexors EMG activities have been measured in each test. In the fatigue protocol, the subjects have repeated several sets of drawings. The subject was asked to rate his/her fatigue level according to the rating scheme of the Borg Scale. The subjects have repeated the drawing set till exhalation. The researchers has asked to archers who perform the drawing action to provide a score from 0 to 10. EMG recordings 1 s prior the fall of the clicker have been analysed and their Median Frequency values have been calculated in Matlab. Differences between two test session were analysed in paired samples t-tests. Results: According to the results of the study, there were significant differences in DM and DF parts muscles (p<0,05) on the basis of comparisons of the mean values of 12 arrows in test -retest condition. To estimate more acute fatigue effects only values of the first three arrows after fatigue protocol have been included into the statistical analysis In this way there were significant differences between T.Brachii and D. middle test-retest results (p<0,05). Discussion As a result, D. Middle muscle has an importance for stabilising the bow till the archer has pulled the string under his chin prior to the aiming phase and in the release phases to balance the weight of the bow. Insufficient release and instability of the bow can cause bad performance in a competition. In archery, an archer does not use his maximal strength for drawing the string. So recovery process starts after each arrow in the given time allowed. Long lasting fatigue effects were apparent for deltoid muscles and acute fatigue effects could be identified for triceps brachii muscles also. This indicates that resting periods between shots are long enough to recover from acute fatigue in some muscles but fatigue effects persist in other muscles. despite recovery periods. These results may help to design recovery strategies in archery shooting.